2022
DOI: 10.1111/cas.15441
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microbiome in gastrointestinal stromal tumors: Looking for different players in tumorigenesis and novel therapeutic options

Abstract: Preclinical forms of gastrointestinal stromal tumor (GIST), small asymptomatic lesions, called microGIST, are detected in approximately 30% of the general population. Gastrointestinal stromal tumor driver mutation can be already detected in microGISTs, even if they do not progress into malignant cancer; these mutations are necessary, but insufficient events to foster tumor progression. Here we profiled the tissue microbiota of 60 gastrointestinal specimens in three different patient cohorts—micro, low‐risk, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…It was also shown that sunitinib itself could induce a significant shift in the microbiome that could affect further treatment [ 107 ]. Recent data has also shown that tissue microbial composition of GIST and microGIST exhibit a difference in the abundance of various bacteria, such as the enrichment of Proteobacteria in GIST samples, hypothesising that the microbiome restructuration can drive the carcinogenesis process [ 108 ]. While microbiome studies are scarce in the GIST, the microbiome likely plays a significant role during the treatment with TKI or immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It was also shown that sunitinib itself could induce a significant shift in the microbiome that could affect further treatment [ 107 ]. Recent data has also shown that tissue microbial composition of GIST and microGIST exhibit a difference in the abundance of various bacteria, such as the enrichment of Proteobacteria in GIST samples, hypothesising that the microbiome restructuration can drive the carcinogenesis process [ 108 ]. While microbiome studies are scarce in the GIST, the microbiome likely plays a significant role during the treatment with TKI or immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The postulated mechanisms by which GISTs cause bacterial infections include systemic invasion via mucosal breakdown by the tumor or concurrent travel of the bacteria through a vehicular-mediated mechanism involving tumor translocation [ 14 ]. Emerging studies have also noted a relationship between gut microbiota dysbiosis and the development of GIST, which we would recommend further exploration [ 19 ]. Nonetheless, if there is a concern for liver metastasis, it is recommended that patients undergo diagnostic workup for pyogenic liver abscesses as well, so they are promptly initiated on appropriate antibiotics [ 18 ].…”
Section: Discussionmentioning
confidence: 99%